2022
DOI: 10.1097/dcr.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institution Analysis of Targeted Colorectal Surgery Enhanced Recovery Pathway Strategies That Decrease Readmissions

Abstract: BACKGROUND: Decreasing readmissions is an important quality improvement strategy. Targeted interventions that effectively decrease readmissions have not been fully investigated and standardized. OBJECTIVE:The purpose of this study was to assess the effectiveness of interventions designed to decrease readmissions after colorectal surgery.DESIGN: This was a retrospective comparison of patients before and after the implementation of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…[7][8][9][10][11] We previously showed that a readmission intervention bundle including updated preadmission education, a mobile phone application, a pharmacist-led pain management plan, and an early postdischarge clinic significantly decreased emergency department (ED) visits and readmissions after colorectal surgery. 12 However, there was no significant difference in these outcomes for patients with AKI, most of whom were patients who underwent new ileostomies. Difficulty monitoring ileostomy output, nonadherence to antimotility algorithms, lack of assistance managing the ileostomy, barriers to home intravenous (IV) fluids, and home health care nursing limitations are some of the possible contributions to dehydration/AKI and readmissions in this population of patients.…”
Section: Principales Medidas De Resultadomentioning
confidence: 93%
See 1 more Smart Citation
“…[7][8][9][10][11] We previously showed that a readmission intervention bundle including updated preadmission education, a mobile phone application, a pharmacist-led pain management plan, and an early postdischarge clinic significantly decreased emergency department (ED) visits and readmissions after colorectal surgery. 12 However, there was no significant difference in these outcomes for patients with AKI, most of whom were patients who underwent new ileostomies. Difficulty monitoring ileostomy output, nonadherence to antimotility algorithms, lack of assistance managing the ileostomy, barriers to home intravenous (IV) fluids, and home health care nursing limitations are some of the possible contributions to dehydration/AKI and readmissions in this population of patients.…”
Section: Principales Medidas De Resultadomentioning
confidence: 93%
“…13,14 We previously showed that ERP revisions that include a mobile phone application, a pharmacist-led pain management plan, and an early postdischarge clinic visit within 4 to 7 days after discharge decrease readmissions after colorectal surgery. 12 However, the time to readmission for the ileostomy patient population was extended from within 1 week to 2 weeks without decreasing the readmission rate, thereby identifying an opportunity for new ERP quality improvement interventions. The results of this study justify the ERP resource investment focused on improving outcomes for patients after colorectal surgery with new ileostomies.…”
Section: Discussionmentioning
confidence: 99%
“…Seven RCTs and 6 nonrandomized cohort studies reported appropriate data on ED visits (Figure 4). The pooled estimate for all studies revealed a decrease in the number of ED visits in the telemedicine group (RR, 0.78; 95% CI, 0.65-0.94). This result showed moderate heterogeneity ( I 2 = 46%).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, retrospective design and large samples of observational studies have ecological validity and provide additional information on how different technologies and settings may affect the outcomes. In addition, some nonrandomized studies have an appropriate prospective design, sufficient power, and adjustments for several potential sources of bias . Second, it was not possible to identify the specific mechanisms of action underlying the observed differences between telemedicine and conventional care groups; however, this study provided some indications of specific mechanisms that may inform future research.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced recovery pathways (ERPs) and minimally invasive surgical approaches have contributed to improved outcomes and decreased hospital length of stay (LOS) after colorectal surgery. 1 Robotic colectomy patients are now frequently discharged on postoperative day 1 or 2 and this has led to reports suggesting feasibility of same-day discharge. [2][3][4][5][6][7] Discharge on the same day after surgery has not yet been widely adopted and the benefit when compared to an overnight hospital stay is still under investigation.…”
Section: Introductionmentioning
confidence: 99%